The Influence of Accounting Information Systems, Work Motivation, Internal Control and Human Resource Competence on the Quality of Financial Reports at the Regional Financial Agency of East Nusa - Fransiskus Marlon Reu; Wizaldy Fabiano Hilnicputro; Afriani Gemar (Journal of Economy, Accounting and Management Science (JEAMS), 2025)
This study aims to determine the effect of accounting information systems on the quality of financial reports at the NTT Provincial Regional Financial Agency, the effect of work motivation on the quality of financial reports at the NTT Provincial Regional Financial Agency, the effect of internal control on the quality of financial reports at the NTT Provincial Regional Financial Agency, the effect of human resource competence on the quality of financial reports at the NTT Provincial Regional Financial Agency, the effect of accounting information systems, work motivation, internal control and human resource competence on the quality of financial reports at the NTT Provincial Financial Agency. This study uses a quantitative method, data collection techniques using questionnaires, sampling in this study was obtained usingpurposive sampling, independent variables in this study are accounting information systems, work motivation, internal control and human resource competence, while the dependent variable in this study is the quality of financial reports. The analysis techniques used are multiple linear analysis tests, descriptive statistical tests, research instrument tests, classical assumption tests and hypothesis tests. The results of the study indicate that the accounting information system has a significant effect on the quality of financial reports at the NTT Provincial Regional Financial Agency, work motivation does not have a significant effect on the quality of financial reports at the NTT Provincial Regional Financial Agency, internal control has a significant effect on the quality of financial reports at the NTT Provincial Regional Financial Agency, HR competence has a significant effect on the provision of credit at the NTT Provincial Regional Financial Agency, accounting information system, work motivation, internal control and HR competence have a simultaneous effect on the quality of financial reports at the NTT Provincial Regional Financial Agency.